(untitled) (BIRDEM Medical Journal, 2019)
Background: Gall bladder cancer (GBC) is a burning topic of discussion in the recent era of laparoscopic cholecystectomy. In 1% of patients undergoing cholecystectomy for cholelithiasis, an incidental gallbladder carcinoma is discovered. Reports of laparoscopic cholecystectomies for cholelithiasis have resulted in earlier discovery of gallbladder cancer. So an increasing number of gall bladder cancer patients in earlier stage are now attending physicians and surgeons. These patients have an excellent chance of survival if aggressively and appropriately managed. Radical cholecystectomy is the only potentially curative therapy for this group of patients. It is crucial to make proper treatment decisions early, rather than after a cholecystectomy - an operation that is incomplete except for the earliest stage of the disease.Present study is a small document about the various presentations and management of gall bladder cancer. It will highlight the options available to patients in Bangladesh which is certainly in line with the internationally accepted standard treatment. Methods: This observational study included patients with confirmed gall bladder malignancy (pre-operative, intra- operative or post- operative) presenting in Hepato-Bialiary-Pancreatic Surgery unit (HBPS), of Bangladesh institute of Diabetes, Endocrine and Metabolic Disorders (BIRDEM) Hospital, in 2004-2005. The patients were diagnosed with detail history, proper clinical examinations and appropriate investigations. The disease status was staged and the patients were appropriately counselled. Patients presenting in stage Ib, II and a few stage III patients underwent loco-regional enblock resection of malignant gall bladder with regional hepatic segments (IVB & V), without violating the cystic plate, skeletonization of hepatoduodenal ligament, clearance of fascia, fat of hepatic hilum with/without excision of bile duct followed by Roux-en-Y hepatico/ cholangio- jejunostomy, where necessary. Patients in advanced stages underwent some form of palliative procedure. All were regularly followed by a standard protocol. Results: This study comprise of 20 consecutive cases of GBC. Three (15%) patients presented with histopathological report of gall bladder malignancy after cholecystectomy. Seven (35%) patients underwent curative enmass resection. Thirteen patients (65%) were offered, appropriate palliative procedure. In this study, 35% cases had a disease free survival of five years. These were the cases in stage Ib & II who underwent a curative radical resection (enmass resection or bisegmentectomy after cholecystectomy). The rest of the patients (65%) had very poor survival. They were the patients in Stage III & IV disease who underwent some sort of palliative procedure with or without chemotherapy. The mean survival in these patients was 7.2 months. Conclusion: With improvements in imaging, staging and hepatic and biliary resection, there is now hope for patients with non-metastatic gallbladder cancer. Radical surgery has been shown to be effective in properly selected patients. It is very important to carry out a proper broad scale study of these cancers in our country. A detailed study will invariably strengthen our efforts to combat this killer disease. More studies need to be done in this context to draw any inference regarding the best way of handling this gloomy condition. Birdem Med J 2019; 9(1): 23-29